Sekolah Perempuan: Langkah Edukasi dan Pemberdayaan dalam Membangun Pengetahuan Serta Kemandirian Para Pekerja Seks Perempuan : (Studi Kasus LSM FKPB Batang) (International Forum of Researchers and Lecturers, 2024)
This article discusses efforts to empower Female Sex Workers (PSP) carried out by the Batang Empowerment Communication Forum (FKPB) through health education and economic training. Counseling in the form of education about HIV/AIDS prevention aims to increase PSP's understanding of the importance of maintaining reproductive health and preventing the spread of disease. Apart from that, economic empowerment is realized through ecoprint batik making workshops, which provide new skills and open up independent business opportunities for PSP. This research uses a qualitative descriptive method with data collection techniques through interviews and direct observation of the activities carried out. The research results show that this combination of health education and economic empowerment not only contributes to increasing PSP's knowledge about health, but also provides opportunities for them to develop more sustainable economic potential. FKPB has succeeded in creating an integrated empowerment model, which integrates health and economic aspects to provide a long-term positive impact on the lives of PSP.